Faktor Yang Mempengaruhi Minat Masyarakat Muslim Yogyakarta untuk Menabung di Bank syariah - Ima Lestari (FAI, 2017)
Faktor Yang Mempengaruhi Minat Masyarakat Muslim Yogyakarta untuk Menabung di Bank syariah